1976
DOI: 10.1111/j.1467-8543.1976.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Manual Worker Wage Earnings

Abstract: THIS article reviews certain empirical results arising from the first phase of an investigation into the manual worker industrial wages structure. The major study will in part draw upon the material presented here in attempting a detailed analysis of earnings determination at the broad industry level. The aim of the present paper is, however, of more modest dimension. It is concerned with wage composition and the principal focus of attention will relate to the 'importance' of basic pay in weekly earning, 1968-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…1 Thus the narrowing of differentials by 8 . It is of particular importance however to note that though the rising trend of 'all other pay' is observed for each of the other male occupations, amongst sales assistants, the occupation most likely to give rise to equal pay problems, 'all other pay' of men fell from 88.…”
Section: Loomentioning
confidence: 97%
See 1 more Smart Citation
“…1 Thus the narrowing of differentials by 8 . It is of particular importance however to note that though the rising trend of 'all other pay' is observed for each of the other male occupations, amongst sales assistants, the occupation most likely to give rise to equal pay problems, 'all other pay' of men fell from 88.…”
Section: Loomentioning
confidence: 97%
“…It is of particular importance however to note that though the rising trend of 'all other pay' is observed for each of the other male occupations, amongst sales assistants, the occupation most likely to give rise to equal pay problems, 'all other pay' of men fell from 88. 1 Thus the narrowing of differentials by 8 . 2 per cent between male and female sales assistants' 'all other pay' seen in Table l(b) has been offset by changes in their methods of wage payment to give a reduction in differentials of only 2.6 per cent measured in terms of gross pay.…”
Section: National Wage Rates and Earnings Composition -mentioning
confidence: 97%
“…The Commission's view of the ineffective nature of industry-wide agreements proved controversial (Elliott and Steele 1976;Addison 1976;Brown and Terry 1978;Elliott 1981). There was implied support from the New Earnings Survey; a later analysis by Elliott and Murphy (1990: 400) found that, for the years 1973, 1975 and 1983, three-quarters or more of male private-sector manual workers were paid basic hourly rates at least 10 per cent more than their appropriate national agreements; and from miscellaneous National Board for Prices and Incomes reports.…”
Section: The Structure Of Bargainingmentioning
confidence: 99%